2004
DOI: 10.1007/s00421-004-1222-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a high-altitude expedition to a Himalayan peak (Pumori, 7,161�m) on plasma and erythrocyte antioxidant profile

Abstract: The effects of a high-altitude exposure were studied in six mountaineers who spent 3 weeks at an altitude range between 5,250 and 7,161 m after 1 week in an acclimatization trek (2,800-5,250 m). Blood drawn from the antecubital vein was collected at sea level 1 day before and 1 day after the expedition to analyse some haematological variables [haemoglobin (Hb), haematocrit (Htc) and red blood cell (RBC) count], erythrocyte antioxidant enzyme activity [superoxide dismutase (SOD), glutathione peroxidase (GPx) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
4
9
0
Order By: Relevance
“…Attempting to emphasize the role of hypoxia, a number of acute, chronic and intermittent hypoxia studies with rats (22,97,106) and humans (7,9,54) have been conducted in both hypobaric and normobaric conditions confirming high-altitude hypoxia per se as an independent modulator of cell and tissue redox status. Data from Magalhães and co-workers in humans and rats, both in plasma (69,73) and skeletal muscle (70)(71)(72) , are consistent with others reporting increased oxidative damage and an inability of the antioxidant system to cope with the increased production of RONS under hypoxia (7,23,52,54,66,77,89,98,106) . Increased lipid peroxidation measured by thiobarbituric acid reactive substances (TBARS) or malondialdehyde (MDA), and enhanced protein oxidation estimated by carbonyl derivatives groups or sulfhydryl groups (SH) were found at distinct levels of cell organization (69)(70)(71)(72)(73) .…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Attempting to emphasize the role of hypoxia, a number of acute, chronic and intermittent hypoxia studies with rats (22,97,106) and humans (7,9,54) have been conducted in both hypobaric and normobaric conditions confirming high-altitude hypoxia per se as an independent modulator of cell and tissue redox status. Data from Magalhães and co-workers in humans and rats, both in plasma (69,73) and skeletal muscle (70)(71)(72) , are consistent with others reporting increased oxidative damage and an inability of the antioxidant system to cope with the increased production of RONS under hypoxia (7,23,52,54,66,77,89,98,106) . Increased lipid peroxidation measured by thiobarbituric acid reactive substances (TBARS) or malondialdehyde (MDA), and enhanced protein oxidation estimated by carbonyl derivatives groups or sulfhydryl groups (SH) were found at distinct levels of cell organization (69)(70)(71)(72)(73) .…”
supporting
confidence: 70%
“…Data from Magalhães and co-workers in humans and rats, both in plasma (69,73) and skeletal muscle (70)(71)(72) , are consistent with others reporting increased oxidative damage and an inability of the antioxidant system to cope with the increased production of RONS under hypoxia (7,23,52,54,66,77,89,98,106) . Increased lipid peroxidation measured by thiobarbituric acid reactive substances (TBARS) or malondialdehyde (MDA), and enhanced protein oxidation estimated by carbonyl derivatives groups or sulfhydryl groups (SH) were found at distinct levels of cell organization (69)(70)(71)(72)(73) . Moreover, DNA damage expressed as increased strand breaks and endonuclease III-sensitive sites was described in human skeletal muscle after 2 weeks of hypoxia (107) .…”
supporting
confidence: 70%
“…Earlier we described a rapid increase in mouse erythrocytes GSH levels on 0.5% O 2 hypoxic exposure in vitro (Bogdanova et al 2003), and others showed an increase in mouse muscle reduced GSH with acute hypoxia equivalent to an altitude of 7000 m (Magalhaes et al 2004), a result that correlates with the observation of suppressed ROS production in hepatocytes primary cultures in response to acute hypoxia (Bogdanova et al 2005). Chronic hypoxic exposure reduces erythrocytes GSH content (Singh et al 2001) and triggers activation of glutathione cycle related enzyme activity (Magalhaes et al 2005) leading to improved antioxidant capacity of blood.…”
Section: Discussionmentioning
confidence: 70%
“…Populations living in the Andes have been exposed to As through drinking water for thousands of years and live at a high altitude, which is associated with increased oxidative stress [46,47]. However, this rural environment is also lacking a number of factors associated with oxidative stress; e.g.…”
Section: Discussionmentioning
confidence: 99%